(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article explores the conceptual essence, theoretical foundations, and structural composition of language competence as one of the central categories in linguistics, psycholinguistics, and language pedagogy. The study emphasizes the role of innate linguistic universals and the learner’s ability to internalize grammatical rules through interaction within the linguistic environment. The author identifies and analyzes the main structural components of language competence — linguistic, sociolinguistic, pragmatic, and strategic — highlighting their interdependence and functional roles in the process of effective communication. Special attention is paid to the motivational and cognitive aspects that ensure the learner’s capacity to produce and interpret language appropriately in diverse social and cultural contexts. The paper concludes that language competence is a multidimensional, dynamic phenomenon that integrates knowledge, skills, and personal attributes necessary for successful linguistic activity and cross-cultural communication.